THE APPLICATION OF BIOCARD TO IMPROVE STUDENTS"™ MOTIVATION IN LEARNING ON THE TOPIC OF TAXONOMY FOR JUNIOR HIGH SCHOOL STUDENTS - Nursapikka, Endi; Yokhebed, Yokhebed (Jurnal Pendidikan Matematika dan IPA, 2019)
The aim of this research is to improve students"™ learning motivation in their learning process by using biocard media on the topic of taxonomy at Junior High School 10 Pontianak. This is a   classroom action research for the seventh grade students in which 10 male students and 20 female students participated. This research was carried out in 2 cycles, the first and second cycle research instruments were questionnaires, each consisted of 20 statements. Based on the results of the first cycle research, students' learning motivation which included in the low category was 6.67%, while the high category was 73.33% and 20% was very high. In cycle 2 there is an increase in students"™ learning motivation that there are no students (0%) who are categorized as low, 10% are in the high category and 90% are categorized very high. It can be concluded that by using biocard media, it can increase students' learning motivation in the taxonomy material.